Experimental and numerical study of fatigue behavior of bridge weathering steel Q345qDNH. (October 2019) - Su, Han; Wang, Jian; Du, Jinsheng
Abstract: Bridge weathering steel produced in China has been used in bridges worldwide. Bridge weathering steel Q345qNH is the most common steel grade used in China and for export, the fatigue crack growth thresholds and fatigue crack growth rate (FCGR) parameters of Q345qDNH are investigated in this paper. The FCGR tests are conducted on 9 compact tension (CT) specimens of base metal and butt welds respectively, the fatigue crack growth threshold tests are conducted on 3 CT specimens of base metal. The fatigue crack growth threshold decreases as stress ratio increases, Q345qDNH has considerably higher fatigue crack growth thresholds than Q345qD and universal thresholds given in BS7910. Two data processing methods are employed to calculate characteristic FCGR parameters. The FCGR parameters determined by small sample method are more conservative than those obtained by group sample method. The FCGR of butt weld increases faster than that of base metal as stress intensity range increases, therefore butt weld is more brittle than base metal. Q345qDNH has slower FCGR than Q345qD and the universal parameters given in BS7910, hence Q345qDNH has better fatigue resistance. The fatigue crack growth was numerically simulated, the largest difference between predicted fatigue life and tested fatigue life is 11.3%, therefore fatigue life can be predicted reasonably accurately by numerical simulation on the basis of measured FCGR parameters, which illustrates the potential and effectiveness of numerical simulation for fatigue assessment of complex bridge structural details based on fracture mechanics and the significance to obtain accurate FCGR parameters. Highlights: Fatigue thresholds and FCGR parameters of Q345qDNH have been measured. Bridge weathering steel Q345qDNH has proved to have excellent fatigue resistance. This paper provides essential data for fatigue assessment of bridges using Q345qDNH. Fatigue life of CT specimens are accurately predicted by numerical simulation.